Characteristics of scientific approaches to the education of children and adolescents in youth sports schools - Mazin, V.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Systematized theoretical concepts of education of children and adolescents in youth sports schools. The characteristics of the planning and situational approach to the organization of the educational process. It is established that the scientists are focusing on the actions of the subject of education. These activities are divided into different areas of education, have one-way and do not provide feedback. It is shown that the scientists focused on targeted reactive actions of the subject of education. Showed inconsistencies between the programmatic approach to the education of children and adolescents in sports activities and the realities of the educational process that takes place on the basis of the solution of educational situations. It is noted that the basis of understanding the educational process it is advisable to put the phenomenon of pedagogical situation. Highlighted a set of conditions and circumstances that are specially created teacher and against which there is a brief interaction of the teacher and the pupil (group).